Asymmetry in media effects on perceptions of police: an analysis using a within-subjects design experiment. (15th January 2021) - Choi, Jaeyong
ABSTRACT: The current study examines the influence of positive, negative, and mixed portrayals of the police in the media on perceptions of police. Participants were randomly assigned to watch an edited video segment from entertainment media. Employing a within-subjects design, participants were surveyed on their perceptions of police, exposed to a video clip, and then re-surveyed. Results from paired-samples t -tests provide evidence concerning media impact on perceptions of police with strong internal validity. The current findings indicate that media exposure can matter, particularly when it introduces negative images of police. Even when mixed images of police were presented, participants were more driven by the negative portrayal. This finding is in line with an asymmetrical impact of negative encounters with police relative to positive encounters.